Guidelines for the building of authority files in development-information systems - Di Lauro, Anne (IDRC OttawaCA)
Contains guidelines for the creation and maintenance of institution authority files (IAF) and for an authority file of country and region names to be used in the production of printed indexes. Describes authority files in general and their function in manual and computerized information systems. Describes the structure and rules of the IAF recommended for development information systems. Contains field-by-field guide to the IAF with rules for form of entry. Presents an authority file for region and country names called the Geographical Authority File.